2022
DOI: 10.3390/biomedicines10040918
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Costimulatory Molecule B7-H4 in the Decidua and Placental Tissues in Patients with Placental Abruption

Abstract: B7 homolog 4 protein (B7-H4), a member of the B7 family, is a immunomodulatory membrane protein. The aim of the study was to evaluate the expression of this protein in the decidua and placental tissues in case of placental abruption (PA) compared to cases of retained placental tissue (RPT) and controls. Tissue samples were obtained from 47 patients with PA, 60 patients with RPT, and 41 healthy controls. The samples were stained for B7-H4 expression, analyzed by an expert pathologist, and a semi-quantitative sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…Steinborn et al observed significantly lower levels of sHLA-G in the patients with placental abruption compared to the levels observed in controls [24], what may lead to increased maternal activation against trophoblast cells. Moreover, placental abruption has been associated with increased fetal monocyte activation [25] and with an alteration in the levels of such suppressive factors as B7H4 and RCAS1 within the feto-maternal interface [26,27]. In our study, the levels of FOXP3-positive lymphocyte infiltration were lower in the chorionic villi derived from the women in the placental abruption group compared to patients after elective CS and patients with PAS.…”
Section: Discussionmentioning
confidence: 39%
“…Steinborn et al observed significantly lower levels of sHLA-G in the patients with placental abruption compared to the levels observed in controls [24], what may lead to increased maternal activation against trophoblast cells. Moreover, placental abruption has been associated with increased fetal monocyte activation [25] and with an alteration in the levels of such suppressive factors as B7H4 and RCAS1 within the feto-maternal interface [26,27]. In our study, the levels of FOXP3-positive lymphocyte infiltration were lower in the chorionic villi derived from the women in the placental abruption group compared to patients after elective CS and patients with PAS.…”
Section: Discussionmentioning
confidence: 39%
“…DIC is di cult to diagnose during pregnancy, yet it can lead to serious adverse outcomes. It arises from concomitant over-activation of the coagulation and brinolytic systems [31], DIC was diagnosed on the basis of brinogen concentration, prothrombin time, and platelet count as described in the present work, the score cut-off of 26 points from that study was also used and the speci city of the diagnosis reached 96% [32].These considerations highlight the need to develop methods to accurately diagnose DIC in a timely manner [33].…”
Section: Discussionmentioning
confidence: 87%